O diretor de escola, o projeto político-pedagógico e a formação de professores em uma escola municipal de ensino fundamental do interior paulista - Tessarin, Marcia Maria de Oliveira (Universidade Federal de São Carlos, 2007)
The school manager as knowledge articulator, using as one of the instruments the Politic Pedagogic Project to formation of your teachers in the school daily, it is the study object of this work (dissertation). The work has as objective to proportion a reflection about of the manager function, as he can organize the school space and the times to formations, discussions and experience exchange as: H.A.C. (Time to Collective Activity), classroom and grade reunion to knowledge management and teaching formation. In the empiric plan, it searches keeping an eye on the manager, the co-coordinator and the teachers in 2005, and consequently the students of Fundamental teaching Municipal School Teacher Francisco Fernando Faria da Cunha, through of school revenue presented in reports. Limited the study of this school about of the initial delegate objectives, it decided utilization of the case study investigation that will permitted through of the interview with the observed school manager of the analysis of documents, occurrences in the school during the searching, a deepening respecting of formation places as Collective Activities Hours, reflection about four classroom and grade reunion, analyze of reports of these reunions and as result, the teacher was positioned as object and agent of your formation, having as eminence three competences: to know relating and to know relating yourself, to know organizing and to know organizing yourself, to know analyzing and to know analyzing yourself; having the school manager effectively as principal character in this process; that is; a reflexive teacher, constructing your action-reflection according the manager your action and organization in the school daily.
Keywords: Escolas organização e administração; Gestão educacional; Educação diretores de escola; Projeto político pedagógico; Professores formação; School manager; Politic pedagogic project; Formation in the school daily; CIENCIAS HUMANAS::EDUCACAO